Resin composition for sealing material, sealing material using the resin composition, and solid polymer fuel cell and water electrolysis device using the sealing material
By using a resin composition including an acrylic resin, an epoxy resin and an epoxy resin curing agent, the problems of insufficient adhesion and poor reworkability of the fuel cell sealing material layer are solved, and efficient sealing and stability are achieved.
Patent Information
- Application Number
- CN202480000724.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-12
- Filing Date
- 2024-02-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-02-06
AI Technical Summary
The existing fuel cell sealing materials are difficult to correct their position after being pasted, and the adhesiveness of the sealing material layer is insufficient, which affects the reworkability and adhesion.
A resin composition is adopted, including an acrylic resin, an epoxy resin and an epoxy resin curing agent, and the glass transition temperature and adhesiveness of the resin are controlled by adjusting the composition and proportion of the resin composition to improve reworkability and adhesiveness.
Good reworkability of fuel cell sealing materials and high adhesion between sealing material layers are achieved, ensuring the sealing and stability of fuel cell.
Smart Images

Figure BDA0004789367650000141 
Figure BDA0004789367650000151 
Figure HDA0004789367660000011
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition for a solid polymer fuel cell sealing material, a sealing material using the resin composition, and a solid polymer fuel cell and a water electrolysis device using the sealing material. Background Art
[0002] A polymer electrolyte fuel cell (hereinafter sometimes referred to as a "fuel cell") generates electricity and heat simultaneously by causing an electrochemical reaction between a fuel gas containing hydrogen and an oxidant gas containing oxygen.
[0003] Figure 1 A cross-sectional view of a cell 10 as a constituent unit of a general fuel cell is shown. A general fuel cell is constructed by stacking tens to hundreds of cells 10. The cell 10 has a sealing material 16 for the purpose of fixing an electrolyte membrane 11 and the like.
[0004] As fuel cell sealing materials, for example, the technologies of Patent Documents 1 and 2 are proposed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-94581
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-2029 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] In recent years, in order to reduce the burden on the environment, it is required to improve the yield rate of each product. Therefore, for fuel cell sealing materials, it is required to have the performance of being able to correct the position after pasting. In this specification, the above performance is sometimes referred to as "reworkability". In Patent Documents 1 and 2, no research has been conducted on reworkability.
[0011] It is believed that the reworkability of fuel cell sealing materials can be improved by reducing the viscosity of the sealing material layer. Figure 2 As shown in FIG. 1 , a cell having regions where the sealing material layers are bonded to each other while facing each other is used. In such a cell, when the viscosity of the sealing material layer is reduced, there is a problem that the adhesion between the sealing material layers is insufficient.
[0012] The technical problem of the present invention is to provide a resin composition for a sealing material that can improve reworkability and improve adhesion between sealing material layers, a sealing material using the resin composition, and a solid polymer fuel cell and a water electrolysis device using the sealing material.
[0013] Solutions for solving the above technical problems
[0014] In order to solve the above-mentioned technical problems, the present invention provides the following [1] to
[11] .
[0015] [1] A resin composition, which is a resin composition for a sealing material,
[0016] The resin composition comprises (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent.
[0017] The glass transition temperature of the acrylic resin (A) is 5° C. to 35° C.,
[0018] The (A) acrylic resin is a copolymer containing raw material monomers of (a1) methyl methacrylate, (a2) styrene and (a3) glycidyl (meth)acrylate,
[0019] The ratio of the (a3) glycidyl (meth)acrylate to the total amount of the raw material monomers is less than 3.0% by mass,
[0020] The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is 1 part by mass or more and 30 parts by mass or less based on 100 parts by mass of the (A) acrylic resin.
[0021] [2] The resin composition according to [1], wherein the epoxy resin (B) is at least one selected from the group consisting of a phenol novolac epoxy resin, a bisphenol A epoxy resin, and a bisphenol F epoxy resin.
[0022] [3] The resin composition according to [1] or [2], wherein the epoxy equivalent of the epoxy resin (B) is 150 g / eq or more and 1500 g / eq or less.
[0023] [4] The resin composition according to any one of [1] to [3], wherein the (C) epoxy resin curing agent is a polyamine curing agent.
[0024] [5] A sealing material formed from the resin composition described in [1].
[0025] [6] A sealing material comprising, in sequence, a first substrate, a sealing material layer, and a second substrate, wherein the sealing material layer is a sealing material layer formed from the resin composition described in any one of [1] to [4], and at least one of the first substrate and the second substrate is removable.
[0026] [7] The sealing material described in [5] or [6] is a sealing material for a polymer electrolyte fuel cell.
[0027] [8] The sealing material described in [5] or [6] is a sealing material for a water electrolysis device.
[0028] [9] A polymer electrolyte fuel cell having a sealing portion formed using the sealing material described in [7].
[0029]
[10] The polymer electrolyte fuel cell according to [9], wherein the sealing material in the polymer electrolyte fuel cell has a sealing material layer formed from the resin composition according to [1], and has regions where the sealing material layers are bonded to each other facing each other.
[0030]
[11] A water electrolysis device comprising a sealing portion formed using the sealing material described in [8].
[0031] Effects of the Invention
[0032] The resin composition for a sealing material, the sealing material using the resin composition, and the polymer electrolyte fuel cell and water electrolysis device using the sealing material of the present invention can improve reworkability and improve adhesion between sealing material layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a cross-sectional view showing an example of a cell constituting a fuel cell.
[0034] Figure 2 This is another example of a cell constituting a fuel cell and is a cross-sectional view showing a part of the cell.
[0035] Figure 3 It is a cross-sectional view showing an example of a sealing material. DETAILED DESCRIPTION
[0036] [Resin composition for sealing material]
[0037] The resin composition for a sealing material of the present invention comprises (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent.
[0038] The glass transition temperature of the acrylic resin (A) is 5° C. to 35° C.,
[0039] The (A) acrylic resin is a copolymer containing raw material monomers of (a1) methyl methacrylate, (a2) styrene and (a3) glycidyl (meth)acrylate,
[0040] The ratio of the (a3) glycidyl (meth)acrylate to the total amount of the raw material monomers is less than 3.0 mol%,
[0041] The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is 1 part by mass or more and 30 parts by mass or less based on 100 parts by mass of the (A) acrylic resin.
[0042] <(A) Acrylic resin>
[0043] (A) The acrylic resin is a copolymer containing raw material monomers of (a1) methyl methacrylate, (a2) styrene, and (a3) glycidyl (meth)acrylate.
[0044] The (A) acrylic resin is a main component of the resin composition. The content of the (A) acrylic resin is preferably 77% by mass to 99% by mass, more preferably 80% by mass to 99% by mass, and even more preferably 85% by mass to 99% by mass, relative to the total amount of the resin composition.
[0045] The (A) acrylic resin needs to have a glass transition temperature of 5° C. to 35° C. If the glass transition temperature is less than 5° C., reworkability cannot be improved. If the glass transition temperature exceeds 35° C., adhesion between sealing material layers cannot be improved.
[0046] The glass transition temperature of the acrylic resin (A) is preferably 5° C. or higher and 27° C. or lower, and more preferably 5° C. or higher and 20° C. or lower.
[0047] The glass transition temperature of the (A) acrylic resin can be adjusted, for example, by the weight average molecular weight of the (A) acrylic resin. There is a tendency that the glass transition temperature becomes higher when the weight average molecular weight increases, and the glass transition temperature becomes lower when the weight average molecular weight decreases.
[0048] In addition, the glass transition temperature of the acrylic resin (A) can also be adjusted by (a4) ethyl (meth)acrylate described later. If the ratio of (a4) ethyl (meth)acrylate to the total amount of the raw material monomers is increased, the glass transition temperature tends to be lower, and if the ratio of (a4) ethyl (meth)acrylate to the total amount of the raw material monomers is decreased, the glass transition temperature tends to be higher.
[0049] In this specification, the weight average molecular weight refers to a value measured by gel permeation chromatography (GPC method) and calculated in terms of polystyrene.
[0050] 《(a1) Methyl methacrylate》
[0051] By including (a1) methyl methacrylate as a raw material monomer of the acrylic resin (A), effects such as the following i) to iii) can be expected. On the other hand, if the content ratio of (a1) methyl methacrylate is too high, the hardness of the sealing material layer becomes high, and it is sometimes difficult to follow the shape of the adherend. Therefore, it is preferred to adjust the content ratio of (a1) methyl methacrylate in consideration of the balance between the effects of the following i) to iii) and the hardness of the sealing material layer.
[0052] i) Since the glass transition temperature of (A) acrylic resin can be finely adjusted, the adhesion and bonding conditions between materials with different polarities can be easily controlled. If the content ratio of (a1) methyl methacrylate increases, the glass transition temperature of (A) acrylic resin tends to rise. As polar materials, the electrolyte membrane of fuel cells can be cited, and as non-polar materials, components other than the electrolyte of fuel cells can be cited.
[0053] ii) Since the weight loss of the (A) acrylic resin due to decomposition by water and acid can be suppressed, the reduction in the cohesive force and adhesive force of the sealing material under high temperature and high humidity can be easily suppressed.
[0054] iii) Since the softening point of the (A) acrylic resin can be increased, the workability when used as a sealing material can be improved.
[0055] The content of (a1) methyl methacrylate is preferably 10% by mass to 45% by mass, more preferably 15% by mass to 40% by mass, and further preferably 20% by mass to 35% by mass, based on the total amount of the raw material monomers.
[0056] 《(a2) Styrene》
[0057] Styrene is a non-polar component whose constituent elements are composed of CH, so it is easy to make the adhesion between materials with different polarities good. In addition, the glass transition temperature of styrene is higher, so the cohesive force of the resin combination can be improved, so it is easy to make the heat-resistant adhesiveness of the resin combination good. And then, by including styrene, the viscosity of the sealing material layer can be easily reduced. On the other hand, if the containing ratio of (a2) styrene is too high, the hardness of the sealing material layer becomes high, and it is sometimes difficult to follow the shape of the adherend. Therefore, it is preferred to consider the balance of the hardness of the above-mentioned effect and the sealing material layer to adjust the containing ratio of (a2) styrene.
[0058] As a common method for imparting heat-resistant adhesiveness to a resin composition, a method of mixing additives such as a silane coupling agent and a tackifier into a resin can be cited. However, in the method of mixing additives, there is a situation where the additives ooze out from the sealing material layer. On the other hand, in the method of using (a2) styrene as the raw material monomer of the (A) acrylic resin, it is preferred from the aspect of not causing the problem of oozing out.
[0059] The content of (a2) styrene is preferably 1% by mass to 30% by mass, more preferably 5% by mass to 25% by mass, and further preferably 10% by mass to 20% by mass, based on the total amount of the raw material monomers.
[0060] 《(a3) Glycidyl (meth)acrylate》
[0061] The (A) acrylic resin needs to contain less than 3.0 mol% of (a3) (meth) glycidyl acrylate relative to the total amount of the raw material monomers. When the content ratio of (a3) (meth) glycidyl acrylate is 3.0 mol% or more, the adhesion between the sealing material layers cannot be improved. On the other hand, when (a3) (meth) glycidyl acrylate is not included as the raw material monomer of the (A) acrylic resin, the reworkability cannot be improved.
[0062] (a3) The content of glycidyl (meth)acrylate is preferably 0.1% by mass or more and less than 3.0% by mass, and more preferably 0.5% by mass or more and 2.0% by mass or less, based on the total amount of the raw material monomers.
[0063] As the glycidyl (meth)acrylate, any of glycidyl acrylate and glycidyl methacrylate can be used appropriately, and from the viewpoint of polymerization versatility, glycidyl methacrylate is more preferably used.
[0064] 《(a4) Ethyl (meth)acrylate》
[0065] The (A) acrylic resin preferably further contains (a4) ethyl (meth)acrylate as a raw material monomer. By containing (a4) ethyl (meth)acrylate, the glass transition temperature of the (A) acrylic resin can be easily adjusted to 35° C. or less.
[0066] In order to easily adjust the glass transition temperature of the acrylic resin (A) to 5°C or more and 35°C or less, the content of (a4) ethyl (meth)acrylate is preferably 30% by mass or more and 95% by mass or less, more preferably 40% by mass or more and 85% by mass or less, and even more preferably 50% by mass or more and 75% by mass or less, relative to the total amount of the raw material monomers.
[0067] As the ethyl (meth)acrylate, any of ethyl acrylate and ethyl methacrylate can be used appropriately, and ethyl acrylate is more preferably used from the viewpoints of easy copolymerization, industrial versatility, and easy adjustment of the softening point.
[0068] Other monomers
[0069] (A) The raw material monomers of the acrylic resin may further contain other monomers. Examples of the other monomers include acrylic acid, methacrylic acid, 2-hydroxymethacrylate, acrylamide, and methacrylamide.
[0070] (A) The acrylic resin is a copolymer obtained by copolymerizing raw material monomers.
[0071] Examples of the copolymerization method include suspension polymerization, emulsion polymerization, solution polymerization, etc. Among these copolymerization methods, suspension polymerization is more suitable from the perspectives of obtaining a polymer having a narrow molecular weight distribution and less residual monomers, obtaining a high molecular weight polymer, having less impurities because an emulsifier is not required, and easily obtaining a copolymer resin having excellent water resistance and heat resistance.
[0072] As the polymerization conditions, for example, in the case of suspension polymerization, it is preferable to perform the polymerization at 50 to 80° C. for 2 to 24 hours.
[0073] The copolymer may be in any form such as alternating, random, block, or graft.
[0074] In aqueous suspension polymerization, one or more suspension stabilizers may be used, for example, water-soluble polymers such as polyvinyl alcohol, partially saponified polyvinyl alcohol, polyvinyl pyrrolidone, (meth)acrylates, polyacrylamide, partially saponified polyacrylamide, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and inorganic salt powders such as calcium phosphates and calcium carbonate.
[0075] As the polymerization initiator, it is preferred that the polymerization initiating radical species after decomposition is oil-soluble.
[0076] As the radical polymerization initiator, an azo radical polymerization initiator or a peroxide radical polymerization initiator may be mentioned as a typical radical polymerization initiator.
[0077] Examples of the azo radical polymerization initiator include 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl)diacetate, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-aminopropane) nitrate, 2,2'-azobisisobutane, 2,2'-azobisisobutyramide, 2,2'-azobisisobutyronitrile, 2,2'-azobisisobutyronitrile, Methyl bis-2-methylpropionate, 2,2'-dichloro-2,2'-azobisbutane, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobisisobutyric acid dimethyl ester, 1,1'-azobis(1-methylbutyronitrile-3-sulfonate sodium salt), 2-(4-methylphenylazo)-2-methylmalononitrile, 4,4'-azobis-4-cyanovaleric acid, 3,5-dihydroxymethylphenylazo-2-allylmalononitrile, 2,2'- Azobis-2-methylvaleronitrile, 4,4'-azobis-4-cyanovaleric acid dimethyl ester, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobis-1-chlorophenylethane, 1,1'-azobis-1-cyclohexanecarbonitrile, 1,1'-azobis-1 -cycloheptanenitrile, 1,1'-azobis-1-phenylethane, 1,1'-azobisisopropylbenzene, ethyl 4-nitrophenylazobenzylcyanoacetate, phenylazodiphenylmethane, phenylazotriphenylmethane, 4-nitrophenylazotriphenylmethane, 1,1'-azobis-1,2-diphenylethane, poly(bisphenol A-4,4'-azobis-4-cyanovalerate), poly(tetraethylene glycol-2,2'-azobisisobutyrate), etc.
[0078] Examples of the peroxide-based radical polymerization initiator include acetyl peroxide, cumyl peroxide, t-butyl peroxide, propionyl peroxide, benzoyl peroxide, 2-chlorobenzoyl peroxide, 3-chlorobenzoyl peroxide, 4-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, 4-bromomethylbenzoyl peroxide, lauroyl peroxide, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, t-butyl peroxytriphenylacetate, t-butyl hydroperoxide, t-butyl performate, t-butyl peracetate, t-butyl benzoate, t-butyl perphenylacetate, t-butyl peroxy-4-methoxyacetate, and t-butyl peroxy-N-(3-tolyl)carbamate. Examples of the polymerization initiator include peroxides such as benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, di-t-butyl peroxide, and methyl ethyl ketone peroxide.
[0079] In addition, a mercapto compound can be added as a chain transfer agent. For example, chain transfer agents having a hydroxyl group such as mercaptoethanol, mercaptopropanol, mercaptobutanol, mercaptopropylene glycol, mercaptobutylene glycol, hydroxybenzenethiol and its derivatives; 1-butylmercaptan, butyl-3-mercaptopropionate, methyl-3-mercaptopropionate, 2,2-(ethylenedioxy)diethylmercaptan, ethylmercaptan, 4-methylbenzenethiol, dodecylmercaptan, propanethiol, butanethiol, pentanethiol, 1-octanethiol, cyclopentanethiol, cyclohexanethiol, thioglycerol, 4,4-thiobisbenzenethiol, etc. can be mentioned.
[0080] The weight average molecular weight of the acrylic resin (A) is preferably 100,000 to 1,000,000, more preferably 150,000 to 800,000, and even more preferably 200,000 to 600,000.
[0081] When the weight average molecular weight is 100,000 or more, the adhesive force in a high temperature environment can be easily improved. When the weight average molecular weight is 1,000,000 or less, gelation during polymerization can be easily suppressed.
[0082] The epoxy equivalent of (A) acrylic resin is preferably 2000g / eq or more and 30000g / eq or less, and more preferably 4000g / eq or more and 20000g / eq or less. By making the epoxy equivalent of (A) acrylic resin 2000g / eq or more, it is possible to easily make the adhesion between the sealing material layers good. By making the epoxy equivalent of (A) acrylic resin 30000g / eq or less, it is possible to easily improve the cohesive force of the sealing material layer. By improving the cohesive force of the sealing material layer, when the water contained in the electrolyte membrane is vaporized and released during hot pressing, it is possible to easily suppress the foaming of the sealing material layer.
[0083] The resin composition of the present invention needs to contain (B) an epoxy resin and (C) an epoxy resin curing agent in addition to the above-mentioned (A) acrylic resin.
[0084] Furthermore, in the resin composition of the present invention, it is necessary to make the total content of (B) epoxy resin and (C) epoxy resin curing agent be 1 mass part or more and 30 mass parts or less relative to 100 mass parts of (A) acrylic resin. By making the total content of (B) epoxy resin and (C) epoxy resin curing agent be 1 mass part or more, reworkability can be easily made good. By making the total content of (B) epoxy resin and (C) epoxy resin curing agent be 30 mass parts or less, the adhesion between the sealing material layers can be easily made good.
[0085] The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is preferably 1 to 25 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the (A) acrylic resin.
[0086] The active hydrogen equivalent (g / eq) of the epoxy resin curing agent (C) is preferably 0.8 or more and 1.2 or less relative to the epoxy equivalent (g / eq) of the epoxy resin (B).
[0087] <(B) Epoxy resin>
[0088] The epoxy resin (B) may be any one or more selected from phenol novolac epoxy resin, bisphenol A epoxy resin and bisphenol F epoxy resin. Among them, phenol novolac epoxy resin has low water absorption and is therefore preferred in terms of excellent temporal stability of the adhesiveness of the sealing material layer.
[0089] The epoxy equivalent of the epoxy resin (B) is preferably 150 g / eq to 1500 g / eq, more preferably 150 g / eq to 1000 g / eq. When the epoxy equivalent of the epoxy resin (B) is 1500 g / eq or less, it is easy to disperse uniformly in the acrylic resin (A).
[0090] The weight average molecular weight of the epoxy resin (B) is preferably 250 to 5000, more preferably 300 to 3000. When the weight average molecular weight is 5000 or less, the epoxy resin (B) can be easily dispersed uniformly in the acrylic resin (A).
[0091] <(C) Epoxy resin curing agent>
[0092] (C) The epoxy resin curing agent may be a polyamine curing agent, an acid anhydride curing agent, a thiol curing agent, a latent curing agent such as an imidazole compound, a ketimine compound, and dicyandiamide, etc. Among them, a polyamine curing agent is preferred because the reaction temperature can be easily lowered.
[0093] Examples of the polyamine curing agent include aliphatic polyamines, aromatic polyamines, polyamidoamines, etc. Among them, aliphatic polyamines are preferred because they can easily lower the reaction temperature.
[0094] The active hydrogen equivalent of the polyamine curing agent is preferably 50 g / eq or more and 700 g / eq or less, and more preferably 75 g / eq or more and 500 g / eq or less. By making the active hydrogen equivalent of the polyamine curing agent 50 g / eq or more, the pot life of the resin composition can be easily extended. By making the active hydrogen equivalent of the polyamine curing agent 700 g / eq or less, the reaction with the epoxy resin (B) is easily carried out, and a resin composition with better durability can be obtained.
[0095] (Other additives)
[0096] The resin composition may contain additives such as a pigment, a flame retardant, a UV absorber, an antioxidant, an antistatic agent, and a silane coupling agent within a range not impairing the effects of the present invention.
[0097] [Sealing material]
[0098] The sealing material of the present invention is formed from the resin composition of the present invention. The sealing material is preferably in the form of a solid such as particles or sheets, and is more preferably in the form of a sheet from the viewpoint of handleability.
[0099] When the sealing material of the present invention is formed into a sheet, it is preferred from the viewpoint of workability to form a sealing material layer by applying a sealing material layer-forming composition prepared by dissolving the resin composition of the present invention in a solvent onto a substrate and drying the composition.
[0100] As an embodiment of the sealing material of the present invention, the following embodiments may be mentioned. Figure 3 It is a cross-sectional view showing the following embodiment. The sealing material of the following embodiment is preferably in a sheet-like form.
[0101] <Embodiment of Sealing Material>
[0102] A sealing material comprising a first substrate, a sealing material layer, and a second substrate in this order, wherein the sealing material layer is formed from the resin composition of the present invention, and at least one of the first substrate and the second substrate is removable.
[0103] Examples of the first substrate and the second substrate include plastic films such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polystyrene, triacetylcellulose, poly(meth)acrylate, polyvinyl chloride, polyphenylene sulfide, and paper, etc. Among them, plastic films are preferred, and polyethylene naphthalate films are more preferred.
[0104] The thickness of the first substrate and the second substrate is preferably 10 μm or more and 100 μm or less, and more preferably 25 μm or more and 75 μm or less.
[0105] In order to facilitate the peeling of at least one of the first substrate and the second substrate from the sealing material layer, the surface is preferably subjected to a release treatment. In order to suppress the adverse effects of the transfer of the release component to the electrolyte membrane and the sealing material layer, the release agent of the release treatment is preferably a non-silicone release agent such as polyolefin.
[0106] The thickness of the sealing material layer is preferably from 10 μm to 500 μm, and more preferably from 20 μm to 200 μm.
[0107] The sealing material of the present invention can be used in the sealing part of a fuel cell, more specifically, in the sealing part of a cell constituting a fuel cell. When used, for example, the sealing material is heated to seal the sealing part of the cell.
[0108] Furthermore, the sealing material of the present invention can also be used for a sealing portion of a water electrolysis device, and more specifically, can be used for a sealing portion of a cell constituting the water electrolysis device.
[0109] [Solid polymer fuel cell]
[0110] The polymer electrolyte fuel cell of the present invention includes a sealing portion formed using the sealing material of the present invention.
[0111] Figure 1 This is a cross-sectional view showing an example of a cell constituting a general fuel cell.
[0112] The battery cell 10 is composed of the following parts: a composite body (MEA: Membrane and Electrode Assembly) consisting of a solid polymer electrolyte membrane 11 and a pair of electrodes (anode and cathode) 12 and 13 arranged on both sides thereof, separators (14, 15) arranged on both sides of the composite body and forming gas flow paths (14a, 15a) for supplying fuel gas and oxidant gas respectively, and a sealing material 16 for sealing the composite body and the separators (14, 15).
[0113] A general fuel cell is constructed by stacking dozens to hundreds of cells 10, sandwiching the stacked body with end plates via current collector plates and insulating plates, and fastening them from both ends with fastening bolts.
[0114] Figure 1 The battery cell 10 does not have a region where the sealing material layers are bonded to each other. Figure 2 As shown, a cell 10 having regions where the sealing material layers are bonded to each other in a facing relationship is also used.
[0115] The sealing material of the present invention can be suitably used as a sealing material in the above-mentioned general-purpose fuel cell. The sealing material of the present invention is particularly suitably used as a sealing material for a fuel cell having a region where sealing material layers are bonded to each other in a facing relationship.
[0116] [Water electrolysis device]
[0117] The water electrolysis device of the present invention comprises a sealing portion formed by the sealing material of the present invention. The sealing portion is preferably a sealing portion of a cell constituting the water electrolysis device.
[0118] Example
[0119] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples.
[0120] 1. Measurement and evaluation
[0121] The following measurements and evaluations were performed on the sealing materials of Examples and Comparative Examples.
[0122] 1-1. Reworkability
[0123] The sealing materials of the examples and comparative examples were cut into samples with a width of 2.5 cm and a length of 12.5 cm. A PET film (thickness 25 μm, width 2.5 cm, length 12.5 cm) was overlapped on the sealing material layer of the cut sample and laminated at room temperature to produce sample 1 for evaluation.
[0124] After the evaluation sample 1 was placed at room temperature for 1 minute, the PET film was stretched using a Tensilon type tensile tester at an angle of 90°, a speed of 100 mm / min, and room temperature to measure the peel strength between the sealing material layer and the PET film. It can be said that the smaller the peel strength, the better the reworkability. Samples with a peel strength of 0.050 N / mm or less can be said to have good reworkability.
[0125] 1-2. Adhesion 1 (Adhesion between sealing material layers)
[0126] The sealing materials of the examples and comparative examples were cut into pieces with a width of 5 cm and a length of 10 cm, and two samples were prepared respectively. The two cut samples were overlapped so that the sealing materials were facing each other, and pre-bonded by lamination with a heating roller at 100°C, and then mainly bonded by hot pressing at 140°C, 0.2 MPa, and 30 seconds. After the main bonding, the samples were cut into strips with a width of 1 cm and a length of 10 cm to prepare sample 2 for evaluation.
[0127] One of the cut samples of the evaluation sample 2 was stretched at an angle of 180°, a speed of 10 mm / min, and room temperature using a Tensilon type tensile tester to measure the peel strength between the sealing material layers. Samples with a peel strength of 0.20 N / mm or more were considered to have good adhesion between the sealing material layers.
[0128] 1-3. Adhesion 2 (Adhesion between sealing material layer and electrolyte membrane)
[0129] The sealing materials of the examples and comparative examples were cut into pieces with a width of 5 cm and a length of 10 cm to prepare two samples of each.
[0130] The two cut samples and the electrolyte membrane were overlapped in the following order, pre-bonded by lamination with a heating roller at 100°C, and then mainly bonded by hot pressing at 140°C, 0.2 MPa, and 30 seconds. After the main bonding, the samples were cut into strips with a width of 1 cm and a length of 10 cm to prepare the evaluation sample 3. The electrolyte membrane used was "Nafion NRE-212 (trade name), thickness 50 μm" manufactured by DuPont.
[0131] One of the cut samples of evaluation sample 3 was stretched at an angle of 180°, a speed of 10 mm / min, and room temperature using a Tensilon type tensile tester to measure the peel strength between the sealing material layer and the electrolyte membrane of one of the cut samples. Samples with a peel strength of 0.20 N / mm or more can be said to have good adhesion between the sealing material layer and the electrolyte membrane. When making the evaluation sample of Comparative Example 7, the sealing material layer of the sample foamed, so the peel strength could not be measured.
[0132] <Stacking Order>
[0133] The first substrate of the first cut sample, the sealing material layer of the first cut sample, the electrolyte membrane, the sealing material layer of the second cut sample, the first substrate of the second cut sample
[0134] 1-4. Adhesion 3 (Hot water durable adhesion between sealing material layer and electrolyte membrane)
[0135] The evaluation sample 3 was immersed in a heat-resistant bottle filled with ion exchange water, and then the heat-resistant bottle containing the sample was placed in an oven at 95°C for 500 hours. After 500 hours, the evaluation sample 3 was taken out from the 95°C hot water and placed in a room temperature atmosphere for 24 hours. Then, one of the cut samples was stretched using a Tensilon type tensile testing machine at an angle of 180°, a speed of 10mm / min, and a room temperature atmosphere to measure the peel strength between the sealing material layer and the electrolyte membrane of one of the cut samples. However, after the evaluation sample was taken out from the hot water, the peel strength of Comparative Examples 2 and 3 in which the electrolyte membrane was peeled off could not be measured. Samples with a peel strength of more than 0.50N / mm can be said to have good adhesion between the sealing material layer and the electrolyte membrane. When making the evaluation sample of Comparative Example 7, the sealing material layer of the sample foamed, so the peel strength could not be measured.
[0136] 1-5. Theoretical Tg
[0137] The theoretical Tg of the acrylic resin (A) obtained in the examples and comparative examples was calculated by the following FOX formula. In the following FOX formula, the glass transition temperature of the homopolymer of each monomer constituting the polymer composed of n monomers is Tg i (K), the mass fraction of each monomer is set as W i (W1+W2+…+W i +…W n =1).
[0138] (FOX style)
[0139] 1 / Tg=W1 / Tg1+W2 / Tg2+…+W i / Tg i +…+W n / Tg n
[0140] 2. Production of sealing materials
[0141] <Example 1>
[0142] [(A) Preparation of acrylic resin]
[0143] Into a 1-liter separable flask was placed a uniform mixed liquid containing the following components: 200 parts by mass of water containing 0.2% by mass of polyvinyl alcohol, 10 parts by mass of styrene monomer (ST), 25 parts by mass of methyl methacrylate monomer (MMA), 1 part by mass of glycidyl methacrylate monomer (GMA), 64 parts by mass of ethyl acrylate monomer (EA), 0.1 parts by mass of benzoyl peroxide as a polymerization initiator, and a chain transfer agent for molecular weight adjustment.
[0144] The mixed solution was heated to 70°C under a nitrogen atmosphere while being stirred, and suspension polymerization was performed for 4 hours. Then, water was removed from the suspension by decantation. The solid was filtered by suction while being washed with water, and after the water was drained, it was vacuum dried at 60°C to obtain acrylic resin C as the (A) acrylic resin used in Example 1.
[0145] The weight average molecular weight of acrylic resin C is 31×10 4 Table 1 shows the monomer composition and molecular weight.
[0146] [Preparation of resin composition]
[0147] (A) Acrylic resin, (B) Epoxy resin, and (C) Epoxy resin curing agent were mixed in the ratio shown in Table 2 to obtain the resin composition of Example 1.
[0148] In Table 2, "1" of "type" of (B) epoxy resin is bisphenol A type epoxy resin (weight average molecular weight 370, manufactured by Mitsubishi Chemical Corporation, trade name jER828, epoxy equivalent 185), and "2" of "type" of epoxy resin is phenol novolac type epoxy resin (manufactured by Nippon Kayaku Co., Ltd., trade name NC-3000, epoxy equivalent 270). In Table 1, (C) epoxy resin curing agent is a polyamine curing agent (manufactured by Huntsman Corporation, trade name JEFFAMINE D-400, active hydrogen equivalent 100).
[0149] [Production of sheet-shaped sealing material]
[0150] The prepared resin composition was mixed with methyl ethyl ketone to prepare a coating liquid for forming a sealing material layer. The coating liquid for forming a sealing material layer was applied to a polyethylene naphthalate film having a thickness of 25 μm, and then dried at 100° C. for 2 minutes to form a sealing material layer having a thickness of 20 μm, thereby obtaining the sealing material of Example 1.
[0151] <Examples 2 to 13, Comparative Examples 1 to 8>
[0152] Resin compositions and sealing materials of Examples 2 to 13 and Comparative Examples 1 to 8 were obtained in the same manner as in Example 1, except that the blending ratio and weight average molecular weight of the monomers of the raw materials of the acrylic resin (A) were set to the values in Table 1, and the blending ratio of the acrylic resin (A), the epoxy resin (B) and the epoxy resin curing agent (C) in the resin composition was set to the values in Table 2. The weight average molecular weight of each Example and Comparative Example was adjusted by the amount of the chain transfer agent.
[0153] [Table 1]
[0154] Table 1
[0155]
[0156] ※In Table 1, ST represents styrene, MMA represents methyl methacrylate, EA represents ethyl acrylate, and GMA represents glycidyl methacrylate.
[0157] [Table 2]
[0158] Table 2
[0159]
[0160] According to the results of Table 1 and Table 2, it can be confirmed that the resin composition for the sealing material of the embodiment can make the reworkability good and can make the adhesion between the sealing material layers (adhesion 1) good. Furthermore, it can be confirmed that the resin composition for the sealing material of the embodiment can make the adhesion between the sealing material layer and the electrolyte membrane (adhesion 2 and 3) good.
[0161] Description of Reference Numerals
[0162] 10 cells
[0163] 11 Electrolyte membrane
[0164] 12, 13 Electrodes
[0165] 14, 15 Separators
[0166] 14a, 15a Gas flow path
[0167] 16 Sealing material
[0168] 16a The first substrate
[0169] 16b Sealing material layer
[0170] 16c The second substrate.
Claims
1. A resin composition for a sealing material, characterized in that: The resin composition comprises (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent. The glass transition temperature of the acrylic resin (A) is 5° C. to 35° C., The (A) acrylic resin is a copolymer containing raw material monomers of (a1) methyl methacrylate, (a2) styrene and (a3) glycidyl (meth)acrylate, The ratio of the (a3) glycidyl (meth)acrylate to the total amount of the raw material monomers is less than 3.0% by mass, The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is 1 part by mass or more and 30 parts by mass or less relative to 100 parts by mass of the (A) acrylic resin, The (C) epoxy resin curing agent is a polyamine curing agent.
2. The resin composition according to claim 1, characterized in that The (B) epoxy resin is at least one selected from the group consisting of a phenol novolac epoxy resin, a bisphenol A epoxy resin, and a bisphenol F epoxy resin.
3. The resin composition according to claim 1, characterized in that The epoxy equivalent of the (B) epoxy resin is 150 g / eq or more and 1500 g / eq or less.
4. A sealing material, characterized in that: The resin composition according to claim 1.
5. A sealing material comprising a first substrate, a sealing material layer, and a second substrate in this order, characterized in that: The sealing material layer is a sealing material layer formed of the resin composition according to claim 1, and at least one of the first substrate and the second substrate is releasable.
6. The sealing material according to claim 4 or 5, characterized in that: It is a sealing material for solid polymer fuel cells.
7. The sealing material according to claim 4 or 5, characterized in that: Sealing material for water electrolysis equipment.
8. A solid polymer fuel cell, characterized in that: A sealing portion is provided which is formed by the sealing material according to claim 6.
9. The solid polymer fuel cell according to claim 8, characterized in that: In the polymer electrolyte fuel cell, the sealing material has a sealing material layer formed from the resin composition according to claim 1, and has a region where the sealing material layers are bonded to each other so as to face each other.
10. A water electrolysis device, characterized in that: A sealing portion is provided which is formed by the sealing material according to claim 7.
Citation Information
Patent Citations
Resin composition for solid polymer fuel cell sealing material, sealing material for solid polymer fuel cell using the resin composition, and solid polymer fuel cell using the sealing material
JP2015002029A
Resin composition for solid polymer fuel cell sealant and sealant for solid polymer fuel cell using the resin composition
JP2016094581A
Thermal adhesive tape for touch switch
CN111690336A
Dicing / die boding sheet
JP2005303275A